Prenatal effects of red and blue light on physiological and behavioural parameters of broiler chickens - Angelika Drozdová; Zuzana Kaňková; Boris Bilčík; Michal Zeman (Czech Journal of Animal Science, 2021)
Light during incubation can influence embryonic and postembryonic development of chickens, but the underlying mechanisms are poorly understood. Previous studies have demonstrated that red and blue lights during incubation had opposite effects on the development of embryonic melatonin biosynthesis; red light results in the highest and blue light in the lowest amplitude of the daily rhythm. Therefore, in this study, we investigated if exposure to monochromatic red (632 nm) and blue (463 nm) light during incubation can differently influence growth, selected biochemical (glucose, cholesterol, triacylglycerols) and endocrine (corticosterone and thyroid hormones) traits and behavioural parameters during postembryonic development in broiler chickens. For analysis, we used 10 and 11 hatchlings incubated in red and blue light, respectively and 10 birds per each group (six males and four females) in 3-weeks-old broilers. During the rapid growth phase (days 18, 20 and 21 of age), higher body weight was recorded in broilers incubated under red compared to blue light, whereas endocrine and metabolic traits did not differ between the treatments. The improved growth rate was related to behavioural traits, mainly because chickens incubated in red light exhibited more passive (resting, standing, preening, dust bathing) and less active behaviours (walking, foraging, fighting, wing-flapping) than the blue-light incubated birds. The time spent for eating and drinking and the results of the tonic immobility test did not differ between both groups. Our results suggest that red and blue monochromatic light during incubation can differently program the postembryonic development of broilers, with possible consequences for their growth and welfare.